Lifting Limits: The Impact of Strength Training in Down Syndrome—A Systematic Review and Meta‐Analysis. - Iglesias‐Díaz, Luis; López‐Ortiz, Susana; García‐Chico, Celia; Santos‐Lozano, Alejandro; González‐Lázaro, Javier (Journal of Intellectual Disability Research, 2025)
Background: People with Down syndrome (DS) may exhibit several musculoskeletal disorders, including alterations in muscle tone and activation. Strength training could mitigate the loss of muscle strength and, therefore, improve strength values in this population. Additionally, it may influence health‐related outcomes such as physical function, body composition and biochemical markers. Objective: This systematic review and meta‐analysis of randomised controlled trials (RCTs) aimed to analyse the characteristics and effects of strength training in people with DS. Methods: A search was conducted from inception to 22 April 2025. The methodological quality of the included RCTs was assessed using the 15‐item Tool for the assEssment of Study qualiTy and reporting in EXercise (TESTEX). In addition, the risk of bias was assessed using the Cochrane's risk of bias 2 (RoB2). Results: A total of 10 RCTs (n = 233 participants) were included in the systematic review, of which three (n = 111 participants) could be meta‐analysed. The pooled effect showed statistically significant benefits for upper (mean difference [MD] = 5.66 kg, 95% CI 2.42–8.91) and lower (MD = 20.43 kg, 95% CI 1.76–39.10) body strength. The TESTEX scores for most RCTs ranged from 3 to 12 points. The risk of bias analysis indicated that eight RCTs had a low risk of bias, whereas the remaining studies were classified as high risk. Conclusion: Strength training may significantly improve muscle strength in people with DS. However, further research is needed to assess the long‐term effects on physical function, body composition and biochemical markers.